New ways to use seal deterrents to protect fisheries - Suuronen, Petri; Lehtonen, Esa; Lehmonen, Roope; Helminen, Jani; Hopkins, Juhani (Luonnonvarakeskus, 2025)
Seal populations in the Baltic Sea have grown rapidly and are in conflict with coastal fisheries. Acoustic deterrent devices (ADDs), also known as seal deterrents, have substantial potential to reduce these conflicts by keeping seals away from fishing gear. Deterrents also lower the risk of seals becoming entangled and drowning in fishing gear. The use of seal deterrents requires broad acceptance by society as well as practical and clear rules. All marine mammal species in the Baltic Sea have excellent underwater hearing and are sensitive to excessive underwater noise. The use of ADDs should not cause significant harm to these animals or other marine life. In many ADD applications further research and development work is needed to make them cost-effective, practical and ethically sound. This report presents the benefits and challenges of new seal deterrent applications developed and tested by the Natural Research Resources Institute Finland (Luke) and provides guidelines regarding the appropriate use of deterrents.
Keywords: seals; acoustic deterrent devices; ADD; seal deterrents